Cost‐utility of extracorporeal membrane oxygenation rewarming in accidentally hypothermic patients—A single‐centre retrospective study. Issue 8 (23rd April 2018) - Kosiński, S.; Darocha, T.; Czerw, A.; Paal, P.; Pasquier, M.; Krawczyk, P.; Drwiła, R.; Gałązkowski, R.
Abstract : Background: Extracorporeal membrane oxygenation (ECMO) has become the treatment of choice for severely hypothermic patients in cardiac arrest or acute cardiac failure. Highly specialized ECMO centres have been established, however, no centre has ever reported the costs of extracorporeal rewarming. The aim of this study was to assess the costs of the treatment of patients in Swiss Stage III and IV rewarmed with veno‐arterial ECMO. Methods: A retrospective exploratory cohort study analysed twenty‐nine consecutive patients treated for hypothermia in the Severe Accidental Hypothermia Centre in Cracow, Poland. The main outcome parameters were the overall and specific costs of the ICU treatment of patients rewarmed with veno‐arterial ECMO. The secondary outcome parameter was cost utility, determined by the costs involved for every year of life gained. Costs were processed using the bottom‐up method and classified into six categories. Survivors were followed up after 1 year. Results: The mean cost of VA‐ECMO was$ 5133 USD, which equalled 35% of all ICU expenditures ($14 668 USD). One year after discharge, 13 of 29 patients were still alive (45%). The overall gain of life of the thirteen 1‐year survivors was 28 years, while the mean cost related to treatment with VA‐ECMO for each year of life gained was 1138 USD. Conclusions: In this study, the costs of VA‐ECMO rewarming and intensive care treatment per patient were substantially lower than in other studies reporting ECMO and intensive care treatment of other causes.